REKAYASA PROTOTIPE E-MUSEUM SONGKET UNTUK MELESTARIKAN BUDAYA LOKAL SUMATERA SELATAN - Andryani, Ria (Jurnal Teknologi Technoscientia, 2017)
E-Museum is a digital creative modifications to the museum into an electronic web-based museum that can be accessed via the internet. Utilization of information technology in preserving the culture of the area into one of the strategies in introducing and promoting the cultural wealth of Indonesia to the international world. Development of E-Museum songket into one creative step the nation can do to keep the local culture in South Sumatra that is not lost with age, because the e-museum as a medium of information dissemination museum. Utilization of Web 2.0 technologies, databases, and viewing multimedia displays to show the diversity of types, songket motifs and colors are needed to be able to produce e-museum informative and high art, so reducing the value cultural values contained in the songket. The objective of this research is to build a prototype e-museum songket web-based and multimedia to provide clear information to Indonesian and international community about the local culture in South Sumatra in the form of songket. E-Museum will also be used as a means of preservation and promotion of local culture to the world internasinal South Sumatra. This research has produced a prototype that was developed using SDLC method.